Internal Force Transfer Mechanism and Bearing Capacity of Vertical Stiffener Joints in CFDST Structures - Yufen Zhang; Dongfang Zhang; Krushar Demoha (Advances in Materials Science and Engineering)
This paper firstly studied the internal force transfer mechanism of vertical stiffener joints in concrete-filled double steel tubular (CFDST) frame structures on the basis of finite element modeling (FEM). Analytical models of shear force and bending moment were established through the appropriate material constitutive equations and equilibrium theory. Then, the proposed models were used to predict and evaluate the shear and bending resistance of the vertical stiffener joint. Six joint specimens were tested to verify the rationality of the theoretical models, and the design suggestions for construction were subsequently discussed. The analysis indicated that the vertical stiffener together with the anchorage web played a dominated role in the internal force transfer mechanism. The computed bending resistance obtained by the tension model agreed well with the measured experimental data, and the shear resistance in the panel zone was sufficient to guarantee the ductile failure in the test. The vertical stiffener determined the plastic hinge so as to ensure the strong connection between the CFDST column and the steel beam. The ribbed anchorage web was an effective way of increasing the shear and bending resistance.